Thermophilic bacteria from Peruvian hot springs with high potential application in environmental biotechnology - Valdez-Nuñez, L.F. (2024)
Hot springs are extreme environments in which well-adapted microorganisms with biotechnological applications can thrive naturally. These thermal environments across Peruvian territory have, until now, remained poorly investigated. In this study, two hot springs, El Tragadero and Quilcate, located in Cajamarca (Peru) were selected in order to investigate the biotechnological potential of indigenous thermophilic bacteria. Enrichment and isolation processes were carried out using microbial mats, sediments, biofilms, and plastic polymers as samples. Screening for biosurfactants and siderophores production, as well as for polyethylene terephthalate (PET) hydrolysis was done using culture-dependent techniques. After molecular identification, Bacillus was found as the most abundant genus in both hot springs. Bacillus velezensis was found producing biosurfactants under high-level temperature. Anoxybacillus species (A. salavatliensis and A. gonensis) are here reported as siderophore-producing bacteria for the first time. Additionally, Brevibacillus and the less-known bacterium Tistrella mobilis were found demonstrating PET hydrolysis activity. Our study provides the first report of thermophilic bacteria isolated from Peruvian hot springs with biotechnological potential for the bioremediation of oil-, metal- and plastic-polluted environments.